Method statement on testing of pile foundation / Mohamad Nazmi Ghumat - Ghumat, Mohamad Nazmi (Universiti Teknologi MARA, Perak, 2013)
This report reviews the procedure of pile test on the construction site from the experience and information gained from practical training for 5 months. In this report also explained about the types and new technology in term of using the testing of pile. Numerous benefits are obtained through the development of new technological equipment for pile testing in the construction field. Materials and machinery used vary widely according to the methods and processes that are performed in construction. In addition, this report shows the latest equipment used during the testing. The technology solved construction problems associated with pile foundations, and recommends criteria based on current knowledge. There are some problems that have been identified in terms of the construction of pile, but all the problems have been solved with some suggestions. Hopefully it can help and can improve to expand the construction industry. This report is divided into several sections which consist of an introduction to the background and the background of the construction project. The company background included in this report describes the location of the company, the company operates, the type of companies involved as well as the organization chart and company logo. As a result of the observation, work methods and processes involved in the construction of this high-rise building are very difficult and not as easy as expected. The construction process is quite complicated and involves many parties which need to have expertise and skills in the construction field. Each construction process is done with careful to avoid mistakes. In conclusion, this report will explain more detail about the method of testing on pile and maybe it can give new information practically to the readers.